Knee pain and related health in the community study (KPIC): a cohort study protocol - Fernandes, Gwen Sascha; Sarmanova, Aliya; Warner, Sophie C.; Harvey, H.; Akin-Akinyosoye, K.; Richardson, H.; Frowd, Nadia; Marshall, L.; Stocks, Joanne; Hall, M.; Valdes, Ana M.; Walsh, David A.; et al. (BioMed Central, 2017)
Background: The incidence, progression and related risk factors for recent-onset knee pain (KP) remain uncertain. This study aims to examine the natural history of KP including incidence and progression and to identify possible phenotypes and their associated risk factors. Methods: A prospective community-based cohort of men and women aged 40 years or over within the East Midlands region (UK) will be recruited via a postal questionnaire from their general practices. The questionnaire will enquire about: presence and onset of KP; pain severity (0–10 numerical rating scale (NRS)); pain catastrophizing and neuropathic-like pain (NP) using the painDETECT questionnaires (definite NP scores ≥19–38); risk factors for KP and/or osteoarthritis (OA) (age, body mass index, constitutional knee alignment, nodal OA, index: ring finger length (2D4D) ratio); quality of life (SF12); and mental health (Hospital Anxiety and Depression Scale). Clinical assessments will be undertaken in a sample of 400 participants comprising three groups: early KP (≤3 year’s duration), established KP (>3 years) and no KP. Assessments will include knee radiographs (standing semi-flexed and 300 skyline views); knee ultrasound (synovial effusion, hypertrophy, and Doppler activity); quantitative sensory testing; muscle strength (quadriceps, hip abductor, and hand-grip); balance; gait analysis (GAITrite); and biomarker sampling. A repeat questionnaire will be sent to responders at years 1 and 3. The baseline early KP group will undergo repeat assessments at year 1 (apart from radiographs) and year 3 (with radiographs). Any incident KP individuals identified at year 1 or 3 questionnaires will have clinical and radiographic assessments at the respective time points. Discussion: Baseline data will be used to examine risk factors for early onset KP and to identify KP phenotypes. Subsequent prospective data, at least to Year 3, will allow examination of the natural history of KP and risk factors for incidence and progression. Trial registration: The study was registered on the clinicaltrials.gov portal: NCT02098070) on the 14th of March 2014.